Pengembangan Media Interaktif Renderforest untuk Meningkatkan Hasil Belajar Teks Negosiasi Siswa Kelas X SMK Musda Perbaungan - Susanti, Elvira; Safina, Nila; Kartika, Rika (Medan Resource Center, 2024)
This research aimed to evaluate the effectiveness and feasibility of Render Forest interactive media on negotiation text material for class X at Vocational School Musda Perbaungan. The study involved 32 students as samples and utilized assessments from material and design expert validators. The results showed that the development was categorized as